THE EFFECT OF ACCRUAL MARKET PRICING, FOREIGN OWNERSHIP, FINANCIAL DISTRESS AND LEVERAGE TO THE INTEGRITY OF FINANCIAL STATEMENTS - Malau, Melinda; Murwaningsari, Etty (Economic Annals, 2018)
The purpose of this research is to analyse the effect of market pricing accrual, foreign ownership, financial distress, and leverage on the integrity of financial statements, using multiple regression analysis and logistic regression. The research uses 363 samples, comprising the data of 121 manufacturing companies listed on the Indonesia Stock Exchange over three years, from 2013 to 2015. The results show that market pricing accrual has a significant positive influence on the integrity of financial statements, while a company’s leverage has a significant negative influence. Bankruptcy and foreign ownership have no significant effect on financial statements’ integrity. Based on the research results, when assessing the integrity of financial statements a company’s stakeholders should pay most attention to market pricing accrual and the company’s leverage. In addition, regulators should produce standards or guidelines governing the company’s remit and responsibilities regarding financial statements.